Evaluation of groundwater quality using water quality index and its suitability for assessing water for drinking and irrigation purposes: Case study of Sistan and Baluchistan province (Iran). Issue 4 (19th May 2019) - Abbasnia, Abbas; Yousefi, Nader; Mahvi, Amir Hossein; Nabizadeh, Ramin; Radfard, Majid; Yousefi, Mahmood; Alimohammadi, Mahmood
ABSTRACT: The present study evaluates the groundwater quality for drinking and agricultural purposes and determines physicochemical characteristics of groundwater in the Sistan and Baluchistan province in Iran. In order to investigate the water quality, sampling was done in 654 open dug wells, the chemical parameters were analyzed, and water quality index was determined. In this regard, Langelier saturation index (LSI), Ryznar Stability index (RSI), Puckorius scaling index (PSI), Larson–Skold index (LS), and Aggressiveness index (AI) were considered to determine water suitability for industrial purposes. Finally, the analytical results were taken to generate the numerical spatial distribution of the parameters using the geographic information system (GIS) environment. According to the results, water sources were less corrosive based on AI and PSI, low and light corrosion according to RSI, and corrosion according to the Larsson–Sckold index. The results of the drinking water quality index showed that 1.2% shared extraction wells were classified as excellent, 52.1% as good, 39% as poor, 6% as very poor, and 1.7% as unsuitable for drinking purpose classes. In addition, irrigating water quality index illustrated that 19.9% and 80.1% wells were placed in the "excellent" and "Good" classes, respectively. Also, the quality of water in this study was categorized as brackish.